Legal analysis of the application of raw clause in an agreement - Rustam, Rustam (Jurnal Hukum Volkgeist, 2019)
The standard agreement for its existence is recognized in trade traffic and has become a habit and need of the community. juridically but the standard agreement does not realize the principle of freedom of contract in full. Because consumers to obtain goods or services needed only have two choices, namely accepting or rejecting the standard agreement. While the principle of freedom of contract prioritizes the freedom and equality of every human being. the principle of freedom of contract also implies that the community has the freedom to make agreements in accordance with their respective interests. The principle of freedom of contract is a principle that gives every person the freedom to make or not make an agreement, make an agreement with anyone, determine the contents of the agreement, the implementation and requirements and determine the form of the agreement, namely written or oral. In general, the form of legal protection against the implementation of the standard agreement has been regulated in Article 18 of Law Number 8 of 1999 concerning consumer protection. The regulation is to provide legal certainty to all the needs of consumers / debtors and to defend their rights if they are harmed by business actors especially in the implementation or implementation of standard agreements.